(untitled) (Studia Prawnicze / The Legal Studies, 2000)
Zarówno pojęcie części składowych, jak i pojęcie przynależności są zbyt wąskim ujęciem dla określenia miejsca poszczególnych składników w ramach zorganizowanej całości gospodarczej, jaką jest gospodarstwo rolne w świetle przepisu art. 553 k.c. Gdyby za pomocą tych pojęć można było budować taką całość, gdyby wystarczały one do opisania relacji pomiędzy poszczególnymi składnikami tej jednostki gospodarczej, to wówczas zamieszczenie definicji gospodarstwa rolnego byłoby zbędne. Przyjęcie tezy, że gospodarstwo rolne jest rodzajem przedsiębiorstwa, powoduje, że m.in. przepisy art. 751 k.c. i art. 552 k.c. należałoby zastosować odpowiednio w sytuacji sprzedaży tego gospodarstwa. Both, the concept of components and the concept of appurtenances are too narrow a view to determine the place of individual components within an organised economic unit such as an agricultural holding in the light of the provision of Article 553 of the Civil Code. If it were possible to construct such a whole with the help of these concepts, if they were sufficient to describe the relationship between the individual components of this economic unit, then the inclusion of a definition of a farm would be unnecessary. Adopting the thesis that an agricultural holding is a type of enterprise implies that, inter alia, the provisions of Article 751 of the Civil Code and Article 552 of the Civil Code would have to be applied mutatis mutandis to the situation of the sale of that holding.